Sistem Pendukung Keputusan Metode Simple Additive Weighting (SAW) Pemilihan Vendor Jasa Boga Terbaik pada Pusat Bisnis Universitas Terbuka - Junianto, Mochamad Bagoes Satria; Basri, Hasan (Program Studi Teknik Informatika Universitas Pamulang, 2024)
The Open University Business Center has duties and functions that focus on the management and development of business units that support the operations and financial sustainability of the Open University. One of the policies handled is the selection of catering vendors used at every event in the Open University environment. Selecting the right catering vendor is a crucial factor in ensuring customer quality and satisfaction. There are 12 catering vendors who are partners of the Open University Business Center which are usually only assessed based on the presentation and quality of the food (Taste). In fact, besides these 2 criteria, there are still several other criteria that must be considered such as Punctuality, interest and vendor experience (administration). The SAW method was chosen because of its ability to carry out multi-criteria assessments simply and efficiently. Of the 12 catering vendors who collaborate with the Open University Business Center, a ranking will be given where the vendor with the highest score is considered most appropriate to the needs of the Open University Business Center. With this Decision Support System, it is hoped that the catering vendor selection process can be carried out objectively, transparently and faster so as to support better decision making at the Open University Business Center.